Charles Diehl, Byzantium: Greatness and Decline. Translated from the French by Naomi Walford. With Introduction and Bibliography by Peter Charanis Prof, of History, Rutgers - Κυριακίδης, Στίλπων Π. (Μακεδονικά, 1960)
No abstract